2022
DOI: 10.3390/su14042235
|View full text |Cite
|
Sign up to set email alerts
|

Case Study Research to Foster the Optimization of Supply Chain Management through the PSS Approach

Abstract: The optimization of a product’s whole life cycle has become a mandatory task for manufacturers seeking to deal with circular economy requirements while gaining competitiveness in the market. In order to achieve such a sustainability goal, alignment of production, distribution, and field service activities is needed. In the literature, numerous studies indicate the product–service system (PSS) approach as one of the most promising business models to combine the needs of manufacturers and customers in an efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Based on this classification, which mainly considers the manufacturers' perspective, it should be noted that the APSS approach is the one that can be more beneficial in the case of industrial complex systems (e.g., the so-called hi-tech products), where the role of after-sales services to ensure the functionality of the product and avoid its obsolescence is fundamental. 22,23 For example, the APSS approach is becoming very diffused in the case of equipment set up in buildings and facilities (i.e., escalators, elevators, HVAC [heating, ventilation, and air conditioning] systems, communication and security systems, etc. ), as well as medical equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this classification, which mainly considers the manufacturers' perspective, it should be noted that the APSS approach is the one that can be more beneficial in the case of industrial complex systems (e.g., the so-called hi-tech products), where the role of after-sales services to ensure the functionality of the product and avoid its obsolescence is fundamental. 22,23 For example, the APSS approach is becoming very diffused in the case of equipment set up in buildings and facilities (i.e., escalators, elevators, HVAC [heating, ventilation, and air conditioning] systems, communication and security systems, etc. ), as well as medical equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, future research should investigate how to manage aftermarket behaviour. Some studies such as that by Fargnoli et al [72] on use-oriented manufacturers have demonstrated the importance of aftermarket services for optimizing the product life cycle. Some actions such as technical assistance network ownership can contribute to the achievement of a circular economy.…”
Section: Future Direction/policy Recommendationsmentioning
confidence: 99%
“…Meanwhile, low or modest capital and investment costs will substantially support the foundation and empower the conversion to hydrogen by supplying credible rationales and sound justifications for the success of hydrogen as a feasible, sustainable, and reliable alternative fuel in the long-haul trucking industry. Some useful considerations on the above aspects and on the ways to advance the optimization of supply chain management using, for instance, the productservice system (PSS) method, aiming at combing the needs of manufacturers and customers in an efficient and effective manner, can be found in [48,49].…”
Section: Hydrogen Refuelling Station Total Investment Costsmentioning
confidence: 99%